Understanding sprint phase-specific training stimuli: a cluster analysis approach to overload conditions - Jiménez-Reyes, Pedro; van den Tillaar, Roland; Castaño-Zambudio, Adrián; Gleadhill, Sam; Nagahara, Ryu (Frontiers in Sports and Active Living, 2024)
This study analyzed the impact of various overload conditions on sprint performance compared to free sprinting, aiming to identify the loading scenarios that most closely replicate the mechanics of unresisted sprints across the full acceleration spectrum. While velocity-based training methods have gained popularity, their applicability is limited to the plateau phase of sprinting. To address this limitation, we employed cluster analysis to identify scenarios that best replicate the mechanical characteristics of free sprinting across various overload conditions. Sixteen experienced male sprinters performed sprints under six conditions: unresisted, overspeed (OS) and four overloaded conditions inducing a velocity loss (VL) of 10%, 25%, 50% and 65% using a resistance training device with intelligent drag technology. Ground reaction forces and spatiotemporal parameters were recorded for all steps using a 52-meter force plate system for all sprint conditions. Cluster analysis revealed four distinct groups aligning with established sprint phases: initial contact, early-acceleration, mid-acceleration, and late-acceleration. Results showed that heavier loads prolonged the mechanical conditions typical of early-acceleration and mid-acceleration phases, potentially enhancing training stimuli for these crucial sprint components of sprint performance. Specifically, VL50 and VL65 loads extended the early-acceleration phase mechanics to steps 7-8, compared to steps 2-4 for lighter loads. Conversely, lighter loads more effectively replicated late-acceleration mechanics, but only after covering substantial distances, typically from the 11- to 29-meter mark onwards. These findings suggest that tailoring overload conditions to specific sprint phases can optimize sprint-specific training and provide coaches with precise strategies for load prescription. These insights offer a more nuanced approach to resistance-based sprint training by accounting for every step across all acceleration phases, rather than focusing solely on the plateau phase, which accounts for only 20-30% of the steps collected during initial contact to peak velocity depending on the analyzed overload condition.